Sistem Pendukung Keputusan Pemilihan Dokter Gigi Terbaik Menggunakan Metode VIKOR Berbasis Web pada RSUD Berkah Pandeglang - Susilawati; Robby Rizky; Agung Sugiarto (Fakultas Teknologi dan Informatika, 2025)
Hospitals are one of the public institutions that are oriented towards community services. The problem in this study is the poor selection related to the best doctor, namely the lack of approach with the leadership and the poor system. For this reason, the selection of the best doctor at Berkah Pandeglang General Hospital has been done manually by assessing doctors from the number of patient treatments that can be cured, but this method cannot assess a doctor who works professionally and has good quality. The purpose of this research is to award the best doctor. The method used for selecting the best doctor is VIKOR (VIšekriterijumsko KOmpromisno Rangiranje) method. The process to be carried out in this study is to determine the criteria used for determining the best doctor based on performance evaluation and performing health services and collecting these data. Based on the results of the study it is concluded that the performance of dentists consisting of Drg. DHITA HANEDYAWURI, Drg. BERLIANA SITORUS, Sp.BM and Drg. ARISA PERMATA SARI produces a final score in selecting the best dentist using the VIKOR method and the results of the final score determine the first rank, namely Drg. BERLIANA SITORUS, Sp.BM